Violent extremism: a nordic outlook - Rostami, Amir; Edling, Christofer (Lexington Books, 2024)
"This work, by incorporating insights from the social sciences, advances a comprehensive understanding of violent extremism in order to improve prevention and intervention efforts. Although focusing on and using data from Nordic countries, it provides empirical guidelines for policymakers, researchers, and security professionals worldwide"--